KONTRIBUSI ALUMNI ILMU FALAK UIN ALAUDDIN MAKASSAR DALAM PENYEBARAN ILMU FALAK DI KABUPATEN MAROS - Jumiati, Jumiati; Chotban, Sippah (HISABUNA: Jurnal Ilmu Falak, 2025)
Abstract This research discusses the contribution of the Astrology Alumni of UIN Alauddin Makassar in the spread of Astrology in Maros Regency. This research uses a type of qualitative research (field study) by explaining systematically and normatively, as well as accurately regarding the object at the heart of the problem. In answering this problem the author uses a syar'ı approach because it is related to Islamic law in the Al-Quran. Hadith on the rules of Ushul Figh and the opinions of the ulama that are in accordance with these problems. Data collected by making observations. interviews, and documentation. The results of this research indicate that UIN Alauddin Makassar Alumni play an important role in spreading knowledge and understanding about astronomy in Maros Regency. They actively hold outreach activities, training, seminars and discussions to strengthen the public's understanding of astronomy and increase awareness of the importance of practicing astronomy in everyday life. Apart from that, Alumni also act as consultants and advisors to the community in determining the beginning of the month, Qibla direction and prayer times. Their contribution has had a positive impact in increasing public knowledge and awareness about astronomy in Maros Regency. Based on the results of field research related to the contribution of the Astrology Alumni of UIN Alauddin Makassar in the spread of astronomy science in the district. Maros, where the people of the district. Maros still doesn't know what astronomy is, they even say that this science is still relatively new, therefore here are some suggestions from researchers: A). For the local government of Maros Regency or the community in the Regency. Maros is always active in providing outreach and counseling to the public so that they understand the importance of astronomy in everyday life. B). For the people in the district. Maros, who still doesn't understand Falak Science, should invite Ilinu Falak alumni to collaborate with the Ministry of Religion in their respective villages to hold seminars, lectures, workshops or outreach activities either in government institutions or educational institutions. So that you get impulsive community guidance from seniors or astronomy graduates.